2019
DOI: 10.1097/aln.0000000000002753
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane Modulates Hippocampal Cornu Ammonis Pyramidal Neuron Excitability by Inhibition of Both Transient and Persistent Sodium Currents in Mice

Abstract: Background: Volatile anesthetics inhibit presynaptic voltage-gated sodium channels to reduce neurotransmitter release, but their effects on excitatory neuron excitability by sodium current inhibition are unclear. The authors hypothesized that inhibition of transient and persistent neuronal sodium currents by the volatile anesthetic isoflurane contributes to reduced hippocampal pyramidal neuron excitability. Methods: Whole-cell patch-clamp recordings of sodium currents of hippocampal cornu ammonis pyramidal neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 66 publications
(78 reference statements)
1
18
0
Order By: Relevance
“…Accumulating evidence suggests that neuroinflammation and anaesthetics play critical roles in cognitive impairment [6567]. However, the divergence in results from various studies demonstrates that the underlying mechanism needs to be further investigated [68–70]. In the present study, LPS-impaired object recognition and fear learning were not aggravated by ISO in adult mice, which suggested that a single use of ISO would not increase memory deficits in young patients with acute abdominal inflammation.…”
Section: Discussionmentioning
confidence: 47%
“…Accumulating evidence suggests that neuroinflammation and anaesthetics play critical roles in cognitive impairment [6567]. However, the divergence in results from various studies demonstrates that the underlying mechanism needs to be further investigated [68–70]. In the present study, LPS-impaired object recognition and fear learning were not aggravated by ISO in adult mice, which suggested that a single use of ISO would not increase memory deficits in young patients with acute abdominal inflammation.…”
Section: Discussionmentioning
confidence: 47%
“…Sodium channels are important for determining the neuronal excitability and action potential (AP) discharge in the CNS (Eijkelkamp et al, 2012;Wang et al, 2017). Volatile anesthetics at clinically relevant concentrations inhibit voltage-gated sodium channel (Na v ) currents in transfected cells (Herold et al, 2009;Yamada-Hanff and Bean, 2015;Zhou et al, 2019), nerve terminals (Ouyang et al, 2003;Yamada-Hanff and Bean, 2015), dorsal root ganglia (DRG) (Scholz et al, 1998;Zhou et al, 2011), and hippocampal neurons (Zhao et al, 2019). Isoflurane reduces AP amplitude and frequency (Wu et al, 2004;Zhao et al, 2019), which may also be mediated by inhibition of sodium channels.…”
Section: Introductionmentioning
confidence: 99%
“…An analogous decrease in membrane excitability was observed in cortical, hippocampal and thalamic neurons in vivo during a barbiturate-induced isoelectric brain state (Altwegg-Boussac et al 2014, 2016, as well as in cortical neurons and motoneurons experiencing elevated doses of isoflurane in vitro (Berg-Johnsen & Langmoen, 1987, 1990El-Beheiry & Puil, 1989b;Sirois et al 1998). This reduced cell excitability could result from the V m hyperpolarization (Shu et al 2003;Altwegg-Boussac et al 2014) and/or from the inhibitory action of isoflurane on sub-threshold sodium currents (Sirois et al 1998;Zhao et al 2019). Augmented values of threshold current were accompanied by a robust enhancement (by ∼45%) of the neuronal gain, contrasting with the attenuation or stability of F-I curve slopes in the barbiturate model (Altwegg-Boussac et al 2014).…”
Section: Partial Alteration Of Cellular and Sensory Responsivenessmentioning
confidence: 69%